2021
DOI: 10.1097/pgp.0000000000000767
|View full text |Cite
|
Sign up to set email alerts
|

MLH1/PMS2-deficient Endometrial Carcinomas in a Universally Screened Population: MLH1 Hypermethylation and Germline Mutation Status

Abstract: MLH1/PMS2 loss due to epigenetic hypermethylation of the MLH1 promoter is the most common cause of mismatch repair deficiency in endometrial carcinoma, and typically provides reassurance against an associated germline mutation. To further characterize the genetic features of MLH1/PMS2-deficient endometrial cancers, the departmental database was searched for cases with dual MLH1/PMS2 loss and retained MSH2/6 expression which underwent MLH1 hypermethylation testing. Genetic testing results were obtained when ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Cost analysis estimated the expense of MLH1-PHM testing to be CAD 231.90 per case, totaling CAD 123,834.60 for the 534 cases, along with significant time and labor burden for the pathology laboratory. MLH1 non-methylated cases comprised 3.3% (14/418) of MLH1/PMS2-d cases and 0.56% (14/2504) of all cases; this was consistent with prior studies indicating DNA methylation accounts for the vast majority of MLH1/PMS2-d ECs [24]. MMR testing in EC is essential for molecular subtype classification and for LS screening.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Cost analysis estimated the expense of MLH1-PHM testing to be CAD 231.90 per case, totaling CAD 123,834.60 for the 534 cases, along with significant time and labor burden for the pathology laboratory. MLH1 non-methylated cases comprised 3.3% (14/418) of MLH1/PMS2-d cases and 0.56% (14/2504) of all cases; this was consistent with prior studies indicating DNA methylation accounts for the vast majority of MLH1/PMS2-d ECs [24]. MMR testing in EC is essential for molecular subtype classification and for LS screening.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, in the context of LS screening, it has been recommended that if MLH1 protein loss is noted on IHC, MLH1-PHM testing is reflexively performed to differentiate between sporadic and hereditary MLH1 loss [6,23]. Germline MLH1 defects are rare in EC and the likelihood of a concurrent germline mutation and hypermethylation is generally thought to be relatively low [24]. Therefore, the presence of MLH1-PHM is considered a negative predictor of LS, limiting the need for consultations in cancer genetic clinics and germline analysis to exclude LS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three endometrial carcinomas have been reported in patients with RAD51C mutations: 1 uterine serous type 4 , 1 type unspecified 7 , and 1 type I endometrial carcinoma (grade not specified) 12 . Along with the 3 reports of endometrial carcinomas in families with RAD51D c.620C>T mutations, 7 additional patients with endometrial carcinoma have an associated mutation in RAD51D : 1 patient with endometrioid-type FIGO grade 3 13 , 2 uterine serous or serous-like carcinomas 5,11 , 2 patients with c.580del mutations (histologic type not specified) 7 , 1 synchronous endometrial and ovarian carcinoma (endometrial type not specified, ovarian carcinoma reported as endometrioid-type FIGO grade 3) 10 , and 1 “mesonephric” copy-number low carcinoma 11 . A different gene, RAD51 (also known as recombinase protein A and located on chromosome 15), has a single-nucleotide polymorphism that is associated with many cancer types and has the highest odds ratio for endometrial cancer risk (range 4–18, depending on model used) 16–18 .…”
Section: Discussionmentioning
confidence: 97%
“…Genes in the RAD51 complex have been associated with different types of cancers, with RAD51C and RAD51D, 2 paralogs on chromosome 17, most closely linked with tubo-ovarian cancer (high-grade serous carcinoma) and breast cancer (with a high proportion of triple-negative phenotypes) (7)(8)(9)(10). In the literature, rare cases of germline RAD51C or RAD51D mutations have been reported in association with endometrial carcinoma, specifically serous, endometrioid, and unspecified histologic types of endometrial carcinoma (4,5,7,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%